CURRENT ISSUES OF TEACHING THE SUBJECT OF HOSPITAL PEDAGOGY IN HIGHER EDUCATIONAL INSTITUTIONS AND ITS METHODOLOGICAL - Safarova Sanobar Omontashevna. (Miasto Przyszłości, 2024)
The article discusses current reforms and innovations in the education system for sick children in need of long-term treatment, as well as the features of teaching children at the Mehrli Maktab school, organized at the Center for Oncology, Hematology and Immunology.